Favorable prognostic significance of membranous β-catenin expression and negative prognostic significance of cytoplasmic β-catenin expression in pancreatic cancer - Rosova, Blanka; Proks, Jan; Filipova, Alzbeta; Hadzi Nikolov, Dimitar; Chloupkova, Renata; Richter, Igor; Szabo, Arpad; Rozsypalova, Aneta; Matej, Radoslav; Melichar, Bohuslav; Buchler, Tomas; Dvorak, Josef (Neoplasma, 2023)
The aim of this study was to investigate the prognostic significance of membranous β-catenin and cytoplasmic β-catenin expression in pancreatic cancer patients (pts). One hundred pts with histologically verified exocrine pancreatic ductal adenocarcinoma were retrospectively studied. The membranous β-catenin, cytoplasmic β-catenin, and cell nucleus β-catenin expression were immunohistochemically evaluated. The expression of membranous β-catenin was <5% in none of the pts, 5-25% in one patient, 26-50% in 2 pts, 51-75% in 14 pts, and >75% in 81 pts. The expression of cytoplasmic β-catenin was <5% in 34 pts, 5-25% in 42 pts, 26-50% in 18 pts, 51-75% in 3 pts, and >75% in one patient. The expression of β-catenin in the cell nucleus was negative in all pts. At the time of the last follow-up, 21 pts were alive and 79 pts had died. Median OS was 1.3 (0.4-2.3) years in pts with membranous β-catenin expression ≤75% and 1.7 (1.3-2.1) years in pts with membranous β-catenin expression >75% (p=0.045). Median OS was (1.3-2.0) 1.6 years in pts with cytoplasmic β-catenin expression ≤25% and 0.9 (0.5-1.2) years in pts with cytoplasmic β-catenin expression >25% (p=0.040). In the univariate Cox proportional hazard models HR (95% CI) was 0.556 (0.311-0.995) in pts with membranous β-catenin expression >75% (p=0.048) and 2.200 (1.216-3.980) in pts with cytoplasmic β-catenin expression >25% (p=0.009). The present results indicate a favorable prognostic significance of membranous β-catenin expression in pancreatic cancer.
Keywords: duktální karcinom slinivky břišní; beta-katenin; retrospektivní studie; Pancreatic Neoplasms; Humans; nádory slinivky břišní; prognóza; Retrospective Studies; Carcinoma, Pancreatic Ductal; beta Catenin; Prognosis; lidé